A tangible interface for 3D character animation using augmented reality technology - Pantuwong, Natapon (My University, 2017)
Nowadays, several systems have been proposed to reduce the difficulty of computer animation authoring. The 3D motion capture system could be used to record the motion data from real actors. The recorded motion could be used to drive an animation. Although this technique reduces the difficulty of computer animation, a user still needs to interact with 3D environment through mouse and keyboard which are 2D interface devices. This paper presents a novel interaction technique for 3D character animation control. A user does not need to interact with typical mouse and keyboard to control an animation, but interacts with a tangible object attached with several visible markers. Our system exploits a benefit of the Augmented Reality technology. The user could see the character movement on the screen of his/her tablet that records the tangible objects by its camera. The user could also move that tangible object to move the 3D character. We also use the Augmented Reality to assist the use for animation scene decoration. Our use study confirms that the proposed interaction technique could reduces the difficulty of 3D character animation, and our system could be by everyone.